1997
DOI: 10.2307/2275579
|View full text |Cite
|
Sign up to set email alerts
|

Decidability of Scott's model as an ordered ℚ-vectorspace

Abstract: Let L = 〈<, +, hq, 1〉q∈ℚ where ℚ is the set of rational numbers and hq is a one-place function symbol corresponding to multiplication by q. Then the L-theory of Scott's model for intuitionistic analysis is decidable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Definition 4.1(3). To handle quantification over the natural numbers we shall use the L ‐definition of N+ found in [2] (cf. § 5 below).…”
Section: Outline Of the Proof Of Theorem 11mentioning
confidence: 99%
See 1 more Smart Citation
“…Definition 4.1(3). To handle quantification over the natural numbers we shall use the L ‐definition of N+ found in [2] (cf. § 5 below).…”
Section: Outline Of the Proof Of Theorem 11mentioning
confidence: 99%
“…In the papers [11, 12], Scowcroft showed that the validity in the model of certain ‐sentences of the language L of ordered rings is also decidable. We proved the decidability of Scott's model restricted to the language of ordered double-struckQ‐vectorspaces in [2] and that proof indeed used, via Rabin's theorem, the decidability of the underlying topological structure. But the full real algebraic structure turned out to be undecidable.…”
Section: Introductionmentioning
confidence: 99%
“…In [5] he showed that the universal fragment of the order structure is decidable. Other decidable fragments of the model were described in the papers of SCOWCROFT ( [6] and [7]) and in [2]. These results led to decidability results in the constructive and intuitionistic theory of reals (cf.…”
Section: Introductionmentioning
confidence: 96%